Citizens’ satisfaction towards the quality of e-filing service / Nur Qaiyisha Suhardi and Normalina Mahmud - Suhardi, Nur Qaiyisha; Mahmud, Normalina (2018)
This research was about the citizens’ satisfaction towards the quality of E-Filing service. The purpose of this research was to identify the citizens’ satisfaction towards the quality of E-Filing, the relationship between tangibility, reliability, responsiveness, assurance and empathy which were the independent variables that could influence and lead to the citizens’ satisfaction which was the dependent Variable. The sample chose was 155 respondents. Researchers used stratified sampling technique to determine the number of sample size and distributed self-administered questionnaires. In analysing the findings, researcher used descriptive statistic, pearson correlation and multiple regression by using Statistical Package for Social Science (SPSS) version 22.0. The result indicated that there was a significant relationship between tangibility, reliability, responsiveness, assurance, empathy and citizens’ satisfaction towards the quality of E-Filing service.